2007
DOI: 10.1111/j.1530-0277.2007.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Many Infants Prenatally Exposed to High Levels of Alcohol Show One Particular Anomaly of the Corpus Callosum

Abstract: An average of the images for the unexposed subjects has the geometry of textbook images of normal babies; but the average for the subgroup of high-angle subjects may serve as a template or guide to this regional damage parallel to the familiar photographic exemplars that help to assess facial signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…In this context, the CC has been suggested having an important role in coordination of motor planning and control, with a bearing on both bimanual and unimanual performance, and in auditory interhemispheric transfer. Furthermore, magnetic resonance imaging (MRI) studies have repeatedly found abnormalities in CC regions in children exposed prenatally to alcohol (Bookstein et al, 2002(Bookstein et al, , 2007Sowell et al, 2001). Even in the absence of significant morphometric Developmental Psychobiology differences, DTI and magnetic resonance spectroscopy (MRS) studies have reported abnormal development of white matter and altered metabolism in the CC in young adults with FAS/FASD, possibly associated with neurobehavioral deficits due to disrupted connectivity (Fagerlund et al, 2006;Ma et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this context, the CC has been suggested having an important role in coordination of motor planning and control, with a bearing on both bimanual and unimanual performance, and in auditory interhemispheric transfer. Furthermore, magnetic resonance imaging (MRI) studies have repeatedly found abnormalities in CC regions in children exposed prenatally to alcohol (Bookstein et al, 2002(Bookstein et al, , 2007Sowell et al, 2001). Even in the absence of significant morphometric Developmental Psychobiology differences, DTI and magnetic resonance spectroscopy (MRS) studies have reported abnormal development of white matter and altered metabolism in the CC in young adults with FAS/FASD, possibly associated with neurobehavioral deficits due to disrupted connectivity (Fagerlund et al, 2006;Ma et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Structural abnormalities of the CC are frequently observed in children with FAS/FASD (e.g., Bookstein, Sampson, Connor, & Streissguth, 2002;Bookstein et al, 2007), including relative white matter reduction (Sowell et al, 2001). At the microstructural level, one study using diffusion tensor imaging (DTI) has reported affected white-matter integrity of the CC in young adults with FAS in terms of less fractional anisotropy and higher diffusion coefficients compared with controls (Ma et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Recent reviews show clearly that PAE in humans produces gross CNS abnormalities including microencephaly and heterotoplasia, and that some developing CNS regions are particularly sensitive to ethanol, including corpus callosum [61][62][63]. MRI and DTI studies have shown anomalies in white matter [4-6, 64, 65] that may in part reflect abnormal myelination.…”
Section: Protective Effects Of Cytokinesmentioning
confidence: 99%
“…These changes have also been reported to persist into adulthood (Kitayama et al 2007;Choi et al 2009) and have been hypothesized to explain emotional regulation difficulties observed in adult victims (Choi et al 2009). Smaller CC volumes are also found in babies born of alcoholic mothers (Bookstein et al 2007) which may constitute a confounding factor. Findings for the PFC have been inconsistent, with one reporting no difference (De Bellis et al 1999) while two more recent studies found larger grey matter volume in the middle-inferior and ventral PFC regions (Richert et al 2006;Carrion et al 2009).…”
Section: Introductionmentioning
confidence: 99%